Early Attention Problems and Children’s Reading Achievement: A Longitudinal Investigation - RABINER, DAVID (2000)
OBJECTIVES: To determine whether attention problems predict the development of reading difficulties and examine whether screening for attention problems could be of practical value in identifying children at risk for reading underachievement. METHOD: Three hundred eighty-seven children were monitored from kindergarten through fifth grade. Standardized assessments of attention problems and reading achievement were conducted at multiple time points. RESULTS: Attention problems predicted reading achievement even after controlling for prior reading achievement, IQ, and other behavioral difficulties. Inattentive first graders with normal reading scores after kindergarten were at risk for poor reading outcomes. CONCLUSIONS: Attention problems play an important role in the development of reading difficulties for some children, and screening for attention problems may help identify children at risk for reading difficulties.